Modulation of microbially derived short-chain fatty acids on intestinal homeostasis, metabolism, and neuropsychiatric disorder - Xiao, Suwei; Jiang, Shu; Qian, Dawei; Duan, Jinao (Applied microbiology and biotechnology, 2020)
A diverse range of symbiotic gut bacteria codevelops with the host and is considered a metabolic “organ” that not only facilitates harvesting of nutrients from the dietary components but also produces a class of metabolites. Many metabolites of gut microbes have an important impact on host health. For example, an inventory of metabolic intermediates derived from bacterial protein fermentation may affect host physiology and pathophysiology. Additionally, gut microbiota can convert cholesterol to bile acids and further into secondary bile acids which can conversely modulate microbial community. Moreover, new research identifies that microbes synthesize vitamins for us in the colon. Here, we will review data implicating a major class of bacterial metabolites through breaking down dietary fiber we cannot process, short-chain fatty acids (SCFAs), as crucial executors of alteration of immune mechanisms, regulation of metabolic homeostasis, and neuroprotective effects to combat disease and improve health.